Uso da história da trigonometria como elemento facilitador da aprendizagem das funções seno e cosseno: um estudo de caso - Souza, Carlos Antonio de (2012)
Based on the understanding that the concepts of sine and cosine function were built during the historical process and that this process took centuries to mean what today represents, seems coherent suspect that the knowledge of this story remove such concepts supposedly zone abstraction and lack of clarity, favoring learning these concepts and its developments. From this perspective, the basic question of this study is: how use of the History of Mathematics in the process of teaching trigonometry functions sine and cosine, can lead the student to have a more meaningful learning? The objective is to investigate how the history of trigonometry can be constituted as a facilitator of learning the functions sine and cosine, by high school students. Theoretically, this study is based on Cajazeiras (2011), Freire (1996), Moreira (2011), highlighting the teaching and learning process, especially meaningful learning in Boyer (2010), Eves (2008) and Kennedy (1992) that brings information and stories about math trigonometry, among others. From the methodological point of view, the study is a quantitative and qualitative nature, conducted in four phases: a pre-test to check students prior knowledge, the use of courseware named test, a post-test in order to obtain comparative performance data, and a questionnaire probing how the History of Trigonometry help in understanding and learning of sine and cosine functions. This pedagogical experiment involving 21 students, the first year of high school, a federal public school, located in the municipality of Nilópolis/RJ. The results, along with a qualitative treatment, were subjected to statistical treatment appropriate to the nature of information collected. The difference between the averages for students in pre and post-tests used before and after the aforementioned pedagogical experience have been developed, was significantly higher than before, at a significant t test, in favor of the post-test, with a level significance of 0.01. The results of the questionnaire, as well as the subjective question that integrated testing revealed a sensitive approach to quantitative data. Thus, the conclusion of the study shows that the history of mathematics as a facilitator to the teaching of sine and cosine functions, quantitatively and qualitatively, confirming our working hypothesis bet or because the method brought forward in student learning on the content.